Circulating MicroRNAs Associated with Changes in the Placenta and Their Possible Role in the Fetus During Gestational Diabetes Mellitus: A Review - Ninna Leslie Trejo-Gonzalez; Martin Palomar-Morales; Luis Arturo Baiza-Gutman; Guadalupe Diaz-Rosas; Clara Ortega-Camarillo; Alejandra Contreras-Ramos (Metabolites, 2025)
MicroRNAs (miRs) are epigenetic regulators of several metabolic diseases, including gestational diabetes mellitus (GDM). Objectives: Following a systematic review, we propose a pattern of key circulating miRs associated with placental changes and their potential role in the fetus. Methods: A systematic investigation of studies published between January 2011 and July 2024 was conducted in the PubMed, ScienceDirect, Trip Database, and Wiley databases. A total of 90 articles were analyzed. Results: Two hundred twenty-six circulating microRNAs were identified in women with GDM, and fifty miRs were validated by PCR, with miRs-16-5p, -29a-5p, and -195-5p being the most frequently reported. Interestingly, miR-16-5p was also expressed in the placenta but not in umbilical cord blood or amniotic fluid. Conversely, miR-126-3p was expressed in circulation, the placenta, umbilical cord blood, and amniotic fluid. Several reports describe high expression levels of miR-518d in maternal circulation, umbilical cord blood, and placenta. Controversial results regarding the expression of miR-29a-3p, -137, and -148a-3p were identified when comparing umbilical cord blood and the placenta. Conclusions: In silico analyses suggest that the miR-29 family, as well as miRs-16-5p, -126-3p, -195-5p, and -518b, may be involved in alterations in the heart, brain, and kidneys in the embryo when exposed to a hyperglycemic environment.